Gestational Age Influences the Early Microarchitectural Changes in Response to Mechanical Ventilation in the Preterm Lamb Lung - Oakley, Regina B.; Tingay, David G.; McCall, Karen E.; Perkins, Elizabeth J.; Sourial, Magdy; Dargaville, Peter A.; Pereira-Fantini, Prue M. (Frontiers in Pediatrics, 2019)
Background: Preterm birth is associated with abnormal lung architecture, and a reduction in pulmonary function related to the degree of prematurity. A thorough understanding of the impact of gestational age on lung microarchitecture requires reproducible quantitative analysis of lung structure abnormalities. This study aimed to (1); use quantitative histological software (ImageJ) to map morphological patterns of injury resultant from delivery of a ventilation strategy to the lung at varying gestational ages and (2) to identify associations between gestational age-specific morphological alterations and key functional outcomes. Method: Lung morphology was compared after 60 minutes of a standardized ventilation protocol (40 cmH2O sustained inflation, volume-targeted positive pressure ventilation with positive end-expiratory pressure 8 cmH2O) in lambs at different gestations (119d, 124d, 128d, 133d, 140d) representing the spectrum of premature to term developmental lung states (saccular to alveolar). Age-matched unventilated controls were compared at 124d and 128d gestation. Automated and manual functions of Image J were used to measure key histological features. Correlation analysis compared morphological and functional outcomes in lambs aged ≤ 128d and >128d. Results: The lung morphology of unventilated controls was indistinguishable at 124 and 128d, whilst ventilated lung from 124d lambs exhibited increased numbers of detached epithelial cells and lung tissue compared with 128d lambs. Across the entire developmental spectrum, lambs aged ≤124d exhibited increased lung tissue, average alveolar area and numbers of detached epithelial cells. Alveolar septal width was increased in lambs aged ≤128d. These findings were mirrored in the measures of gas exchange, lung mechanics and molecular markers of lung injury. Correlation analysis differentiated the gestation-specific relationships between the histological assessments and functional measures in ventilated lambs at gestation ≤128d versus >128d. Conclusion: Image J allowed rapid, quantitative assessment of alveolar morphology and lung injury in the preterm lamb model. Gestational age-specific patterns of injury in response to ventilation delivery were identified, with 128d being a transition point for associations between morphological alterations and functional outcomes. These results further support the need to develop individualized respiratory support approaches tailored to both the gestational age of the infant and their underlying injury response.